(untitled) (Journal of Governance and Development (JGD), 2019)
Entrepreneurs have been recognized by many as the catalyst for economic growth and development. Raising women as entrepreneurs is a part of current government initiative. Although women entrepreneurs have become more important players in the entrepreneurial landscape, the number is still small as compared to businesses owned by men. This paper will look into the entreperneurial programs implemented by governmental agencies in Malaysia. After looking at the programs, analysis of the programs will be further discussed. Indeed, this paper found that there are only a number of entrepreneurship programs which are specially designed for women by some selected agencies despites lack of evaluation of existing entrepreneurship programs.